Desigualdade ocupacional e o uso do tempo: um estudo sobre os determinantes do tempo de trabalho remunerado e do tempo livre entre indivíduos adultos inseridos no mercado de trabalho em uma cidade brasileira e nas regiões metropolitanas norte-americanas - Luiz Flávio Neubert (2011)
This study aims to carry out a quantitative analysis of the interplay of the work and the free time activities and the dimension of occupational inequalities. More specifically, the results found by Neubert (2006) were tested using new regression models, with a broader number of occupational variables. The data is drawn from time use studies in: the metropolitan area of Belo Horizonte, Brazil, in 2001, and the United States metropolitan areas in 2003. The main findings indicate the need to discuss the social security issues in the Brazilian labor market, as well as the process of labor flexibilization in the US. These results corroborate the general hypothesis of this study, which argues that the general organization of the week, in which working days differ from non-working days, is a kind of management of time that only applies to specific occupational groups. Key-